Genuine empty follicle syndrome: role of double trigger and delayed oocyte retrieval (DTDO) - Abdul Majiyd Noushin; Sankalp Singh; Aluvilayil Sonia; Swati Singh; Reema Basheer; Raiza Ashraf; Ahmed N Waseem; Mohamed Ashraf (Wolters Kluwer Medknow Publications, 2021)
Background: Empty follicle syndrome (EFS) is a condition of undetermined etiology where no oocytes are retrieved in an ART cycle despite adequate response to ovarian stimulation and diligent follicular aspiration. Because of the rarity of this condition, no much published strategies are available to tackle this. Aim: The aim of this study was to evaluate whether sequential administration of gonadotropin-releasing hormone agonist (GnRHa) and human chorionic gonadotropin (hCG) as a trigger at 40 h and 36 h, respectively, before oocyte retrieval (OCR) could correct genuine empty follicle syndrome (GEFS). Study Setting and Design: This retrospective observational cohort study was conducted in a tertiary fertility center over a period of 6 years from January 2014 to December 2019. Patients with a history of GEFS were administered GnRHa and recombinant hCG subcutaneously at 40 h and 36 h, respectively, before OCR, i.e., double trigger and delayed oocyte retrieval (DTDO) (n = 13). The primary outcome measures studied were number of mature oocytes retrieved, oocyte maturation index (OMI), number of fertilized oocytes, and number of embryos available for embryo transfer. The secondary outcome measures were clinical pregnancy rate (CPR), miscarriage rate (MR) and live birth rate (LBR) per first frozen embryo transfer (FET) cycle, incidence of inadvertent premature ovulation, and ovarian hyperstimulation syndrome. Statistical Analysis: Comparison between the groups was analysed by Fisher's exact test and paired t-test. Results: Patients in the DTDO group showed a significant improvement (P < 0.01) in the number of mature oocytes retrieved, OMI, number of fertilized oocytes, and number of embryos available for embryo transfer. In the first FET cycle, CPR (44.44%), LBR (44.44%), and MR (11.11%) were observed in the DTDO group. Conclusion: Our findings implicate that double trigger and delayed OCR (DTDO) is a safe and efficacious treatment strategy for GEFS.